Aspects of Dental Anxiety at Children of Different Ethnicities - Vlad, Ramona; Monea, Monica; Mircia, Eleonora; Mihai, Adriana (European Scientific Journal, ESJ, 2017)
Objectives: The aim of our study is to identify the differences in how the dental act is perceived among children of different ethnic groups. For this purpose, we started from the hypothesis that the degree of child anxiety at the dentist can be influenced by the socio-economic status of the family of origin. Material and methods: A sample of 115 school children, including 40 Romanian children, 36 Hungarian children and 39 Roma children, aged between 8-9 years old, were interviewed. We have chosen these three ethnic groups to see if there are differences in the perception of the dental act. In terms of psychological method, the questionnaire, the semi-structured interview, and the demonstration were used. Results: The results showed that most children of the Romanian and Hungarian groups had been to the dentist, whereas only 48.71% of the Roma children had been there. The highest degree of anxiety is manifested by the Roma children. There are no significant differences in this study between the answers of Romanian children and Hungarian children regarding the degree of anxiety in the dental office. Conclusions: The study confirmed the hypothesis that the degree of child anxiety at the dentist is influenced by the socio-economic status of the family of origin. When the socio-economic level is low, parents do not go to the dental office for treatment or prevention and this behaviour is passed on to children.